THE IMPACT OF LIFESTYLE MODIFICATION ON THE IMPROVEMENT OF ADOLESCENT REPRODUCTIVE DISORDER WITH PCOS : A LITERATURE REVIEW - Nur Maziyah Hurin'in (Indonesian Midwifery and Health Sciences Journal, 2023)
Polycystic ovarian syndrome (PCOS) is described as a symptom of disturbances in the aspects of reproduction and metabolism. Reproductive disorders usually manifest as hyperandrogenism, irregular ovulation, and polycystic ovaries, leading to decreased fertility. This was a literature review research that writes briefly, concisely and up to date on a topic from scientific publication articles. The purpose of this research was to solve the problem of reproductive disorders in young women with PCOS from the theory studied. Articles were compiled by conducting a library search through Google Scholar and Scientdirect from 2013-2022 with a total of 7 articles. Therapy for improving the body's metabolism is improved so that the function of reproductive hormones is also expected to function properly and normally, so that lifestyle changes become a support for therapy for women with PCO to reproductive hormonal changes related to successful ovulation in adolescent girls with PCOS.